استخدام وسيلة لوحة الجيوب لترقية التحصيل الدراسي في مهارة القراءة لدى الطلاب الصف الثاني أ بالمدرسة المتوسطة الإسلامية الأهلية كوملا أتشيه - Nyak Mustakim; Anis Rina (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2022)
This study aims to determine the use of pocket board media that can improve student learning outcomes in grade 2A MTsS Keumala Aceh in reading skills. The research design used by the researcher in this study is classroom action research with two cycles, where each cycle consists of four stages, namely planning, action, observation and reflection. The data collection instruments used were observation sheets, test questions, and documents. The results showed that the use of question and answer cards media can improve student learning outcomes in grade 2A MTsS Keumala in reading skills, this can be seen from the average value obtained by students in the two cycles carried out by the researchers, namely 62.5 and in the second cycle with a value of 85.83.